WILL THE TYPE OF GnRH ANALOGUE AFFECT THE EMBRYO CLEAVAGE - Gopalakrishnan, Manjula; Reddy N, Sanjeeva; Sinvaniah Surulimuthu, Muthiah (International Journal of Clinical and Biomedical Research, 2015)
Aim and Objective: The present study is aimed to carry out the effect of the type of GnRH analogue on embryo cleavage. Materials and Methods:A total of 403 patients who underwent Intra Cytoplasmic sperm injection were included in the study .They were divided in to three groups. Group I- Embryos which cleaved before 27 hours after injection. Group II- Embryos which cleaved after 27 hours, Group III-Embryos which cleavaed before and after 27 hours. The effects of GnRh agonist and antagonist on embryo cleavage were compared between the three groups. Results: All the 403 patients were analysed. There was no difference in the mean age, duration of ovarian stimulation, number of oocytes retrieved, fertilization, cleavage rates and embryo quality between the three groups. Out of 403 patients, early cleavage was observed in 165 patients (40.94 %). Late cleavage was observed in 129 patients (32.01%), both early and late cleavage was observed in 109 patients(27.05%).Out of 227 patients in the agonist protocol the early cleavage was observed in 98 patients (43.17%), late cleavage was observed in 71patients (31.28%),and both early and late cleavage was observed in58 patients (25.55%). Out of 176 patients in the antagonist protocol the early cleavage was observed in 67 patients (38.07%), late cleavage was observed in 58 patients (32.95%), and both early and late cleavage was observed in 51 patients (28.98%) P 0.563. We observed there was no statistical significant difference between agonist and antagonist stimulation protocol on embryo cleavage Conclusion: The embryo cleavage was not affected by the type of GnRHanalogue used. KEYWORDS: Early cleavage; Embryo quality; Intracytoplasmic sperm injection; Ovarian stimulation.